2022
DOI: 10.33751/jhss.v6i2.5394
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Architecture for Banking in the Industrial Revolution Era 4.0

Abstract: The banking industry must keep up with the latest technological developments. If not, the banking industry will start to be abandoned by customers. This study presents enterprise architecture recommendations for the banking industry in the era of the industrial revolution 4.0. The architecture contained in this research consists of business architecture, information systems architecture, application architecture and technology architecture. The hope is that with the recommended architecture, we can adopt the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The current industry must make a transition to the concept of smart factories. Only few studies were found that address this type of business architecture models [29,35], [85].…”
Section: Rq2: What Are the Proposed Framework For Smart Industry?mentioning
confidence: 99%
“…The current industry must make a transition to the concept of smart factories. Only few studies were found that address this type of business architecture models [29,35], [85].…”
Section: Rq2: What Are the Proposed Framework For Smart Industry?mentioning
confidence: 99%